Prevalence of Reproductive Problems under different Dairy Production Systems - Diksha Patel and K. Ponnusamy, (Indian Journal of Extension Education, 2018)
The present study was conducted in Haryana, Madhya Pradesh and Chhattisgarh representing three differentdairy production systems namely: dynamic, transient and subsistence dairy production systems of Indiarespectively during 2017-18. Data were collected personally, from 30 Veterinary Officers (VO)by personalinterview.Among 10 major reproductive problems of female animals, late sexual maturity with RBQ value 92and anestrus (82) in non-descript; anestrus (94) and late sexual maturity (76) in indigenous; repeat breeding(82) and anestrus (67) in crossbred; and anestrus (94) and repeat breeding (82) in Buffalo were ranked firstand second reproductive problems respectively in Haryana state. Whereas in case of Madhya Pradesh thenon-descript cattle; indigenous cattle; crossbred cattle and buffalo breed were mainly affected by late sexualmaturity (94) and anestrus (88); anestrus (92) and late sexual maturity (85); repeat breeding (88) and anestrus(70) and late sexual maturity (94) and anestrus (87) were ranked by respondents respectively. Late sexualmaturity (78) and uterine infections (77); late sexual maturity (88) and anestrus (85); uterine infections (73)and abortion (67); late sexual maturity (90) and anestrus (83) were ranked the first and second reproductiveproblems in non-descript cattle; indigenous cattle; crossbred cattle and buffalo respectively in Chhattisgarh.Constraints analysis revealed that treatment of dairy animals by village-quacks was the important constraintreported by veterinary officers (V.Os) of Haryana and lack of awareness of farmers for reproductive problemsof dairy animal was the most important constraint as perceived by V.Os of both Madhya Pradesh andChhattisgarh.Sincestate-level variation could be observed in prevalence of reproductive problems as well asconstraints experienced by V.Os; state centric extension plan should be prepared to reduce the prevalence ofreproductive problems of animals and constraints of veterinary officers.